Chronic hypoxia exacerbates diabetic glomerulosclerosis through mesangiolysis and podocyte injury in db/db mice. Issue 10 (29th June 2020) - Takahashi, Naoki; Yoshida, Haruyoshi; Kimura, Hideki; Kamiyama, Kazuko; Kurose, Tomomi; Sugimoto, Hidehiro; Imura, Toshio; Yokoi, Seiji; Mikami, Daisuke; Kasuno, Kenji; Kurosawa, Hiroyuki; Hirayama, Yoshiaki; et al.
Abstract: Background: Chronic hypoxia may play a pivotal role in the development of diabetic nephropathy (DN). However, the precise mechanisms underlying progressive hypoxia-induced glomerular injury remain unclear. Methods: We housed db/db mice in a hypoxia chamber (12% O2 ) for up to 16 weeks beginning at 8 weeks of age. Various urine, serum and kidney abnormalities and glomerular messenger RNA (mRNA) expression were compared with those in age-matched db/db mice housed under normoxia. Results: Levels of urinary albumin and podocalyxin (PCX) were significantly higher in hypoxic mice early during hypoxia. Ultracentrifugation of urine samples revealed that podocytes in the hypoxic mice shed PCX-positive microparticles into the urine. After 16 weeks of hypoxia, the mice also had higher hematocrits with lower serum glucose and various degrees of mesangiolytic glomerulosclerosis with microaneurysms and the infrequent occurrence of nodular lesions. Immunohistologically, hypoxic mice showed significantly decreased endothelial cell densities early during hypoxia and decreased podocyte densities later. In both hypoxic and normoxic mice, glomerular macrophage and transforming growth factor-β1 (TGF-β1) staining significantly increased with aging, without changes in vascular endothelial growth factor or endothelial nitric oxide synthase (eNOS). Glomerular mRNA expression of monocyte chemoattractant protein-1, eNOS and TGF-β1 was significantly enhanced in the hypoxic mice. Conclusions: These results indicate that chronic hypoxia induces advanced glomerulosclerosis with accelerated albuminuria triggered by mesangiolysis and podocyte injury in a murine model of DN.